Test and Evaluation of Autonomous Ground Vehicles. (23rd January 2014) - Sun, Yang; Xiong, Guangming; Song, Weilong; Gong, Jianwei; Chen, Huiyan
Abstract : A preestablished test and evaluation system will benefit the development of autonomous ground vehicles. This paper proposes a design method for a scientific and comprehensive test and evaluation system for autonomous ground vehicles competitions. It can better guide and regulate the development of China's autonomous ground vehicles. The test and evaluation system includes the test contents, the test environment, the test methods, and the evaluation methods. Using a hierarchical design approach, the test content is designed to be stage by stage, moving from simplicity to complexity and from individual modules to the entire vehicle. The hierarchical test environment is established according to the levels of test content. The test method based on multilevel platforms and sensors is put forward to ensure the accuracy of test results. A fuzzy comprehensive evaluation method combined with analytic hierarchy process (AHP) is used for the comprehensive evaluation which can quantitatively evaluate the individual module and the overall technical performance of autonomous ground vehicles. The proposed test and evaluation system has been successfully applied to real autonomous ground vehicle competitions.